KOMPETENSI WANITA PESISIR DALAM PROGRAM PENGEMBANGAN MASYARAKAT DI KECAMATAN ABELI KOTA KENDARI - Selmi, Selmi; Batoa, Hartina; Jayadisastera, Yoenita (Jurusan Penyuluhan Pertanian FP UHO, 2026)
Coastal women play a significant role in supporting family economies and coastal community development. However, this potential has not been optimally utilized through community development programs. The objective of this study is to assess the competence of women residing in coastal communities within Abeli District, Kendari City, in the implementation of community development programs. The study population comprised all coastal women who were actively engaged in community development programs in Abeli District, with a total sample size of 40 individuals. The sampling technique that was employed was a census technique. The data collection techniques employed in this study included surveys, structured interviews, and documentation. The research variable was the competence of women in coastal communities in community development programs. The data were analyzed using quantitative descriptive analysis. The findings indicated that the competence of coastal women in community development programs in Abeli District, Kendari City, was classified as high, as evidenced by the predominance of respondents who exhibited high overall competence levels. Coastal women exhibited notable competencies in a variety of productive roles, consistently producing high-quality work, managing their time effectively, maintaining consistent attendance, and fostering robust cooperation within the group. Coastal women fulfill a multifaceted role in society, encompassing both domestic responsibilities and a strategic economic and social contribution to the success of community development programs. These competencies have been demonstrated to fortify household economic resilience and contribute to the sustainability of coastal community development. The enhancement of community development initiatives, grounded in the competencies of coastal women, is imperative to ensure inclusive and sustainable enhancement of coastal welfare.